Caracterização do desgaste do rebolo na retificação de insertos de metal duro - Rodrigues, Aristóteles Guido (Universidade Federal de São Carlos, 2021)
The cutting tool manufacturing industry constantly seeks to improve its products, due to the high competition in this sector. In this scenario, cemented tungsten carbide cutting inserts stand out for their wide application, related to their excellent cost-benefit ratio in the machining of diverse types of metals. Thus, an increasing knowledge of their manufacturing process variables and their effects is required, being the grinding operation a fundamental step in the search for high efficiency of cutting inserts, as it is responsible for providing the final dimensions as well as appropriate surface and edge quality. Within this context, the present work aims to characterize the wear of a diamond grinding wheel during grinding of cemented tungsten carbide inserts and to assess its effects on the insert surface characteristics with the increase in total material removal volume. For this, a resin bonded wheel with diamond grains D46 was applied and the normal and tangential force components were measured during the process. In addition, the grain protrusion in the abrasive grinding layer, the insert surface and edge roughness were analyzed. The obtained results revealed an initial reduction in the grain protrusion and the consequent increase in the grinding forces with the increase in the volume of removed material. With the grinding of larger volumes, however, the occurrence of self-sharpening was also observed, which led to increased grain protrusion and reduced forces. This phenomenon contributed to the increase in the number of active edges in the abrasive layer and caused a reduction in the insert surface roughness. Little or no variation in edge roughness was identified.
Characterization of wheel wear when grinding carbide inserts
Keywords: Retificação; Rebolo de diamante; Desgaste; Metal duro; Integridade superficial; Grinding; Diamond grinding wheel; Wear; Cemented tungsten carbide; Surface integrity; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO